2021
DOI: 10.1186/s12917-021-02951-5
|View full text |Cite
|
Sign up to set email alerts
|

Leech therapy (Hirudo medicinalis) attenuates testicular damages induced by testicular ischemia/reperfusion in an animal model

Abstract: Background Testicular torsion/detorsion triggers tissue ischemia/reperfusion, leading to reactive oxygen species overgeneration and apoptosis. The saliva of leeches is full of anti-inflammatory, anticoagulants, antioxidants, and antimicrobial agents. Therefore, this study aimed to assess the protective mechanism of leech therapy on testicular ischemia/reperfusion damage. Methods 18 adult male rats were randomly divided into three groups: 1-Sham-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…The results of our study supported similar results for significant decrease in the above testicular tissue cells. Several recent studies have proposed the crucial role of ROS in decreasing the number testicular tissue cells and their vitality [31,32]. In this study, AVP could significantly reverse changes in the number of sperms and increase their vitality.…”
Section: Discussionmentioning
confidence: 52%
“…The results of our study supported similar results for significant decrease in the above testicular tissue cells. Several recent studies have proposed the crucial role of ROS in decreasing the number testicular tissue cells and their vitality [31,32]. In this study, AVP could significantly reverse changes in the number of sperms and increase their vitality.…”
Section: Discussionmentioning
confidence: 52%
“…The injury is commenced following torsion of the spermatic cord that leads to ischemia and intensifies with time (Anim et al, 2005). Several previous studies revealed that damage triggered by reperfusion is more significant than that caused by ischemia (Davoodi et al, 2021;Kölükçü et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, flavonoids, an important class of natural polyphenols, play important roles in inhibiting neuroinflammation, repairing the blood-brain barrier, and inhibiting brain damage [ 52 , 53 ]. Leeches, as the most potent natural thrombin inhibitor, can inhibit oxidative damage and apoptosis induced by tissue ischemia [ 54 , 55 ]. Research showed that hirudin can reduce the accumulation of leukocytes in the brain and shift microglia to the anti-inflammatory phenotype [ 56 ].…”
Section: Discussionmentioning
confidence: 99%